Breaking the Ice: Exploring Healthcare Seeking Behaviors in Junior Hockey - Stephanie Stresing; Andrea Bundon; Moss E. Norman; Desmond McEwan (Sociology of Sport Journal, 2026)
This study explores how elite junior male hockey players in Western Canada engage with health care in the context of sport. Using a constructionist approach, interviews with elite junior hockey players (ages 17–20) explored how masculinity shapes health-seeking behaviors. Despite growing awareness of athlete health, playing through injury was often normalized, reflecting ideals of toughness and stoicism. Two themes, old and new, and authority and influence illustrate how historical and evolving masculinities shape decision making. Coaches, managers, and trainers were identified as key figures who either reinforce or challenge these norms. This research offers insight into how the junior hockey environment impacts help-seeking practices and contributes to broader discussions on masculinity, sport, and athlete well-being.